ANALYSIS FACTORS USING FINANCIAL TECHNOLOGY OF TRADITIONAL MARKET TRADERS (EMPIRICAL STUDIES ON THE TRADITIONAL MARKET IN DINOYO AND GUYUB RUKUN MARKET, MALANG - EAST JAVA) - Ahmad Raihan Hakim; Mochamad Agung Prawiro; Ririn Novianti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This paper aims to analyze the use of information technology in mobile phone platforms (smartphones) at market traders in Malang which represents the Small and Medium Enterprises (SMEs) sector and determine the factors causing the use of financial services on smartphones. The analysis in this paper uses survey research methods with descriptive-statistical analysis and desk study, which takes survey data on 45 (forty-five) market traders in Dinoyo Market and Guyub Rukun Market in Malang, East Java, then the survey results are analyzed to find out the results of how the use of cellular phones in respondents and the factors causing the use of financial services. Based on the results of the analysis, it was found that the simplicity of registration and daily operation are the key factors of respondent decision. Policymakers need to pay attention to the simplicity factor in regulating information technology-based financial services and should be sufficient to conduct socialization so that the intended financial services can be optimized for the community, especially small communities (SMEs).